Association analyses of the INSIG2 polymorphism in the obesity and cholesterol levels of Korean populations - Shin Hyoung; Kim Jae-Ryong; Kim Kil; Park Byung; Choi Sun; Koo Imhoi; Cha Seongwon; Kim Jong (BMC, 2009)
Abstract Background While INSIG2 has been reported to be associated with BMI in many populations, conflicting results have prevented consensus over its role. In analyses of mice and cell cultures the gene has been found to be involved in the regulation of cholesterol synthesis; however, no relationship has been found with cholesterol metabolism in human epidemiological research. Therefore, this study attempts to assess the effect of rs7566605 near INSIG2 on both obesity- and cholesterol-related traits in Koreans. Methods The rs7566605 polymorphism was genotyped with 2,364 Koreans, and associations with obesity- and cholesterol-related traits were analyzed statistically via an ANOVA or T-test. Results Replication of an association with BMI, WHR, fat mass, fat percent, and abdominal fat area failed, and the C allele of rs7566605 was not associated significantly with total cholesterol, HDL cholesterol, or triglyceride. However, it was found in a meta-analysis of a dominant model that the C allele of rs7566605 appeared to affect the level of the total cholesterol, especially in female subjects. Conclusion We failed to show associations of rs7566605 with cholesterol- and obesity-related phenotypes, although we newly suggest the possible involvement of INSIG2 with the plasma level of the total cholesterol in women.